Local Instructional Trajectory: Research-Based Hybrid Learning Assisted by Sevima Edlink in Improving Student Learning Independence - Herlan Sanjaya; Fawziah Zahrawati; Andi Aras (IAIN Manado, 2022)
Local Instructional Trajectory: Research-Based Hybrid Learning Assisted by Sevima Edlink in Improving Student Learning Independence. This study aims to design a local instructional trajectory of Research-Based Hybrid Learning (RBHL) assisted by Sevima Edlink to increase student learning independence. This research is design research consisting of three stages, namely: preliminary design, experimental design, and retrospective analysis. The subjects of this study were 27 students. Furthermore, questionnaires and observation guidelines became data collection instruments. After the data is collected, it is then analyzed. The findings of this study are the PHBP path assisted by Sevima Edlink through 5 stages, namely research focus, research planning, data searching, data processing, research results writing, and presentations carried out online and offline. The following finding is that local instructional trajectory of RBHL can increase student learning independence as seen from the increase in the average learning independence before and after treatment, from 2.40 to 4.28. The findings of this study can be an offer to solve the problem of learning independence of students in the midst of the limitations of offline learning.